Utilization of Activated Corn Cob (Zea Mays) as an Improved Adsorbent for Reducing Chemical Oxygen Demand (COD) Value from Waste of the Sasirangan Industry - Erfan Roebiakto; Noor Hikmah Damayanti; Neni Oktiyani; Nurlailah Nurlailah (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2021)
Liquid waste from sasirangan industrial activities has a high enough Chemical Oxygen Demand pollutant power. If it is directly discharged into water bodies, it can damage the environment and harm health. One of the first processes needs to be done by using activated corn cobs (Zea mays). This study aimed to analyze the ability of corn cobs charcoal to reduce levels of Chemical Oxygen Demand and increase the pH of sasirangan waste so that the results of this study can be an alternative to natural-based sasirangan waste treatment. This type of research is a pure experiment with a research design in One Group Pretest Posttest Design. The research material used was sasirangan industrial waste in Manarap Village, Kertak Hanyar District, Banjar Regency, South Kalimantan, Indonesia. Chemical Oxygen Demand levels were determined by the closed reflux titrimetric method. The results showed that the addition of the highest dose of activated corncob charcoal (50 g) reduced the largest turbidity by 35 percent, increased the pH by 72 percent, and reduced the color intensity by 33 percent. The conclusion is that the addition of corncob-activated charcoal at a dose of 30gr, 40gr, 50gr can reduce levels of Chemical Oxygen Demand, respectively, namely 24 percent, 35 percent, and 33 percent. An increase in pH was found at the same dose of 46 percent, 62 percent, and 72 percent, respectively. There is an effect of increasing the mass of activated charcoal from corn cobs on the Chemical Oxygen Demand levels in the sasirangan industrial waste with a significance value of 0.007. It is suggested to use corn cobs-activated charcoal for the pretreatment stage of sasirangan industrial waste treatment.